Evaluating the scientific accuracy and pedagogical approaches in biodiversity content of secondary school textbooks: A cross-publisher study - Herawati, Desti; Munandar, Rifki Risma; Ganeswara, Muhamad Ginanjar; Nurafsari, Isna (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
This study analyzes how biodiversity is represented in secondary school biology textbooks from both government and private publishers. The focus of the research is on evaluating their alignment with the national curriculum, the scientific accuracy of biodiversity concepts, and their ability to foster critical thinking. The research employs a descriptive content analysis approach using the Four Steps Teaching Material Development (4S TMD) method, limited to the selection stage. The sample consists of one government-published and one private-published biology textbook commonly used in Grade X of Secondary School, selected from a survey of 45 schools in Bogor Regency. The results show key differences: government textbooks provide a more accurate, comprehensive view of biodiversity and are better aligned with the curriculum, offering real-world ecological examples. They also promote inquiry-based learning and critical thinking. On the other hand, private textbooks offer more superficial coverage with conceptual errors, focusing on rote memorization and theoretical knowledge. These findings suggest that government textbooks are better suited for fostering a deep understanding of biodiversity, while private textbooks may limit students' ability to engage with the topic. The study calls for improved quality of textbook biodiversity content better to support students' learning and awareness of ecological issues. Future research could explore the impact of these textbook differences on student outcomes.Abstrak. Penelitian ini menganalisis bagaimana keanekaragaman hayati diwakili dalam buku teks biologi sekolah menengah atas yang diterbitkan oleh penerbit pemerintah dan swasta. Fokus penelitian ini adalah mengevaluasi kesesuaiannya dengan kurikulum nasional, akurasi ilmiah konsep keanekaragaman hayati, dan kemampuannya dalam mengembangkan pemikiran kritis. Penelitian ini menggunakan pendekatan analisis konten deskriptif dengan metode Four Steps Teaching Material Development (4S TMD), yang dibatasi pada tahap seleksi. Sampel terdiri dari satu buku teks biologi yang diterbitkan oleh pemerintah dan satu buku teks yang diterbitkan oleh penerbit swasta, yang umum digunakan di Kelas X Sekolah Menengah Atas, dipilih dari survei 45 sekolah di Kabupaten Bogor. Hasil menunjukkan perbedaan signifikan: buku teks pemerintah memberikan gambaran yang lebih akurat dan komprehensif tentang keanekaragaman hayati, serta lebih selaras dengan kurikulum, dengan contoh-contoh ekologi dunia nyata. Mereka juga mendorong pembelajaran berbasis penemuan dan pemikiran kritis. Di sisi lain, buku teks swasta menawarkan cakupan yang lebih permukaan dengan kesalahan konseptual, berfokus pada hafalan dan pengetahuan teoretis. Temuan ini menyarankan bahwa buku teks pemerintah lebih cocok untuk mengembangkan pemahaman mendalam tentang keanekaragaman hayati, sementara buku teks swasta mungkin membatasi kemampuan siswa untuk terlibat dengan topik tersebut. Studi ini menyerukan peningkatan kualitas konten keanekaragaman hayati dalam buku teks untuk mendukung pembelajaran dan kesadaran siswa terhadap isu-isu ekologi. Penelitian masa depan dapat mengeksplorasi dampak perbedaan buku teks ini terhadap hasil belajar siswa.